Electrical power generation in Antarctica: challenges, opportunities and future work for Turkish Antarctic research station - Shinwari, Muhammad Fahad; Norhafidzah, Mohd Saad; Arslan, Erhan; O¨zsoy, Burcu; Muhamad Zahim, Sujod (KeAi Publishing Communications Ltd., 2025)
Antarctica's extreme environment, marked by frigid temperatures, fierce winds, and prolonged periods of darkness, presents significant challenges for sustaining energy needs at research stations. The Turkish Antarctic Research Station (TARS), located on Horseshoe Island, represents a strategic opportunity to explore renewable energy solutions to overcome logistical, environmental, and operational challenges associated with conventional fossil fuel reliance. This paper provides a comprehensive assessment of the potential for renewable energy (RE) power generation in Antarctica, focusing on challenges, opportunities, and future work for TARS. The study begins with an overview of existing Antarctic stations, highlighting installations with renewable energy systems, such as Princess Elisabeth Station and McMurdo Station. The integration of renewable energy at these facilities underscores the viability and limitations of current technologies. Key challenges, including extreme weather, logistical complexities, and technological barriers, are examined, along with opportunities to harness the continent's abundant wind and solar resources. The paper further proposes a renewable energy framework for TARS on Horseshoe Island. Using Random Forest Regression and Grey Wolf Optimization, optimal sizing and placement for wind, solar PV, and battery systems are determined, considering local weather conditions and future load demands. The proposed system also incorporates advanced energy storage and optimized power flow within the TARS microgrid. This research aims to establish a sustainable energy model for TARS, reduce its carbon footprint, and contribute to global efforts to transition Antarctic research stations towards renewable energy-based solutions.